Retrospective cohort study of Advanced HIV disease among children and adolescents in Uganda: Characteristics, clinical outcomes, and rate of mortality - Calvin Epidu; Rogers N. Ssebunya; Freddrick E. Makumbi; Edgar Sserunkuma; Emmanuel Tumwine; Patrick Kizza; Michael Juma; Henry Balwa; Betty Nsangi; Albert K. Maganda; Denise J. Birungi; Arthur G. Fitzmaurice; et al. (PLoS ONE, 2026)
Background People diagnosed with advanced HIV disease (AHD) are at high risk for mortality even after starting antiretroviral therapy (ART). We determined characteristics, clinical outcomes, and risks of mortality among children and adolescents diagnosed with AHD in western Uganda. Methods We conducted a retrospective cohort analysis of routinely collected program data of children and adolescents living with HIV (CALHIV) aged 0–19 years, from outpatient HIV clinic electronic medical records in 48 high-volume health facilities in two regions of western Uganda (Fort Portal and Hoima). Data for clients who initiated ART during January 2016—July 2023 were analysed. AHD was defined as a CD4 cell count <200 cells/μL, or WHO stage 3 or 4, or any child younger than 5 years of age living with HIV who had been on ART for more than 12 months and virally non-suppressed (≥1,000 copies). We used descriptive statistics (i.e., frequencies and percentages) to summarise characteristics and treatment outcomes. Kaplan-Meier curves were used to estimate survival overall and by clients’ characteristics; log-rank tests were used to compare survival functions. A gamma-shared frailty model was used to determine factors associated with the rate of mortality. Effect measures were summarized using adjusted hazard ratios (aHRs) with corresponding 95% confidence intervals (95%CI). Results A total of 5,143 CALHIV, including 3,067 (59.6%) females, with a median (interquartile range [IQR]) age of 10 (9) years were assessed. Overall, AHD was high (18.1%) and varied by age—0–4 years (68.4%), 5–9 years (12.6%), 10–14 years (13.2%), and lowest among adolescents, 15–19 years (7.7%). Just over half of the CALHIV with AHD were active in care (51.5% [480/932]), about a quarter (26.4% [264/932]) had transferred out, 13.8% (129/932) were lost to follow-up, and 8.3% (77/932) had died. Survival was significantly higher in CALHIV who were not malnourished compared to those with malnutrition (p = 0.001). Overall mortality rate per 100 person-years among CALHIV with AHD was 4.1 (95%CI:3.2–5.2) and was significantly higher among those who had been on ART for 3 months or less (27.3; 95%CI: 20.6–36.2) compared to 6 months or more (1.0; 95%CI: 0.6–1.7). Conclusion Advanced HIV Disease among CALHIV in western Uganda was consistent with what has been published elsewhere. Risk of death differed by nutrition status and was high among those on ART three months or less. Early screening and management of malnutrition, as well as early ART initiation and adherence initiatives, might improve outcomes and reduce AHD-related mortality among CALHIV.